MODEL AFFECTIVE EDUCATION OF CHILDREN IN THE FAMILY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Affective education is part of cognitive and psychomotor development. Affective includes the developers attitudes, values, morals, and emotions. Part of the affective education is to be implemented in the family. Several methods of value socialization are affective, behavior modification, observation, cognitive, sociocultural and apprenticeship. Application methods affective, behavioral modification and observation is more appropriate for younger children. In the implementation of value education in the family there are five short a Tan namely, cultivation, moral development, analysis, clarification of values and learning action. Fifth short a tan need to be applied in accordance with the development of the childs family. In the family quality of relations parent- child, beliefs, perceptions and values of child a lisa the right of parents, and social culture as well as graphical demo factors.